The Influence of K-Pop Fandom on Cross-Cultural Social Identity among Indonesian Teenagers - Asfinawati; Farhan, Muhammad (Mahogany Journal De Social, 2025)
The rapid growth of Korean popular culture, especially K-pop, has transformed global youth culture and reshaped identity formation across national borders. In Indonesia, teenagers represent one of the most active groups of K-pop consumers, engaging not only with music but also with diverse fandom practices that encourage cross-cultural interaction. This study explores the influence of K-pop fandom on the cross-cultural social identity of Indonesian teenagers and views fandom as both a cultural space and a social arena. A qualitative descriptive case study design was employed to capture teenagers’ lived experiences within fandom communities. Data were gathered through semi-structured interviews, participant observation in online and offline fan spaces, and analysis of fan-produced documents. Purposive sampling was applied to select active teenage fans with variation in gender, education, and length of participation. Thematic analysis identified patterns of cultural adaptation, social belonging, and identity construction. The findings show that fandom shapes cultural interests through language learning, adoption of practices, and intercultural awareness. Socially, it strengthens belonging, loyalty, self-expression, and peer networks. However, financial pressure, stereotypes, parental conflict, and competition also arise for many teenagers.